UNIVERSITY THE EFFECT OF REWARDS AND PEER ENVIRONMENT ON STUDENT LEARNING MOTIVATION AT SMKN 2 CIKARANG BARAT - Sarumaha, Yuliana; Yohana, Corry; Fidhyallah, Nadya Fadillah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to determine the effect of rewards and peer environment on student motivation at SMKN 2 Cikarang Barat majoring in Governance & Office Automation. The method used is a survey method. The respondent selection technique uses Proportional Random Sampling which refers to Isaac and Michael's tables so that an affordable population of 316 students is obtained with a sample of 161 students. Respondents studied in this study were students of class X, XI and XII of SMKN 2 Cikarang Barat majoring in Governance & Office Automation. Data were collected through a questionnaire with a Likert scale. Based on the results of research conducted, it was found that rewards have a positive and significant effect on learning motivation. Peer environment has a positive and significant effect on learning motivation. In accordance with the research hypothesis.